SHELLQs-JWST unveils the host galaxies of 12 quasars at z > 6 - Ding, Xu-Heng; Onoue, Masafusa; Silverman, John D.; Matsuoka, Yoshiki; Izumi, Takuma; Strauss, Michael A.; Yang, Lilan; Jahnke, Knud; Phillips, Camryn L.; Treu, Tommaso; Andika, Irham T.; Aoki, Kentaro; et al. (The astrophysical journal, 2025)
The advent of the James Webb Space Telescope (JWST) has opened new horizons in the study of quasar host galaxies during the reionization epoch (z > 6). Building upon our previous initial measurements of stellar light from two quasar host galaxies at these redshifts, we now report the detection of the stellar light from the full Cycle 1 sample of 12 distant moderate-luminosity quasar (M1450 > −24 mag) host galaxies at z > 6 from the Hyper Suprime-Cam Subaru Strategic Program. Using JWST/NIRCam observations at 1.5 and 3.6 μm combined with 2D image decomposition analysis, we successfully detect the host galaxies in 11 of the 12 targets, underscoring the high detection rates achievable with moderate-luminosity quasars. Based on two-band photometry and spectral energy distribution fitting, we find that our host galaxies are massive, with log M*/M⊙ = 9.5-11.0. The effective radii range from 0.6 to 3.2 kpc, comparable to the sizes of inactive galaxies with similar masses at z ∼ 6 as measured with imaging from COSMOS-Web. Intriguingly, the two quasar hosts with post-starburst features, which reside at the high-mass end of our sample and exhibit relatively compact morphologies, have similar size and stellar mass surface densities to quiescent galaxies at z ∼ 4-5. These findings suggest that the so-called galaxy compaction scenario is already in place at the reionization epoch, in which gas inflows during starburst phases drive centrally concentrated star formation followed by rapid quenching, bridging the structural transition of massive galaxies from relatively extended star-forming disks to compact quiescent systems.
Veröffentlicht: 28. Oktober 2025
Gesehen am 02.01.2026